Pendampingan Tutor dalam Menghadapi Implementasi Kurikulum Merdeka di PKBM Pelagi Satya Darma - Anuraga Kusumah; Hartanti Nugrahaningsih; Titing Suharti; Renea Shinta Aminda; Agung Wibowo; Gemy Ghethan (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This activity is intended for PKBM to prepare for the implementation of an independent curriculum, assistance activities for preparation for the implementation of an independent curriculum are carried out at SPS PAUD Pelangi with PKBM participants throughout the Kedung Waringin District. With the policy of implementing an independent curriculum, every organization of educational activities must prepare themselves. This activity aims to provide information and assistance to prepare for the implementation of an independent curriculum. Methodology: This activity is carried out in several stages, namely the first is to provide material on the independent curriculum, the second is the introduction of the stages of implementing the independent curriculum, the third is discussion, and the fourth is trying to implement only one stage of the stages recommended by the Ministry of Education and Culture. Results: The results of this activity illustrate the difficulties experienced by PKBM in dealing with the implementation of an independent curriculum because the lack of socialization has been overcome, PKBM has been able to gradually absorb the implementation stages recommended by the Ministry of Education and Culture.